Does Agriculture Matter for Economic Growth of Uttar Pradesh (India)? - Khan, Waseem; Ansari, Saghir Ahmad (Economy of Regions, 2018)
Twenty-five years have passed since economic reform in India. It brought about many macroeconomic policy changes in the economy. Although these policy changes helped the manufacturing and services sector to grow, agriculture did not get any direct benefits from economic reforms. It was assumed that it would get indirect benefits due to changes in exchange and trade policy, liberal industrial licensing system and reduction in industrial protection, which would benefit tradable agriculture by ending discrimination against it and by turning the terms of trade in its favour. The present study examines the transformation in agriculture and basic contributory roles i. e. product, market, and factor contribution of agriculture in the economy of Uttar Pradesh. Further, a long run association and causal relation between agriculture and other economic sectors and sub-sectors are explored. An understanding of the relationship between agriculture and overall GDP growth becomes important from a policy maker’s perspective, as it would guide the decisions in allocating the scarce resources to attain growth and development. Results show that Product, market, and factor contribution has increased over the years. Empirical estimates show that agriculture is a driver of the unregistered manufacturing sector, transport storage and communication sector; and overall economy as a whole. Public investment in irrigation should be accelerated, cost-effective and yield-raising technology should be accessible to medium and small farmers. Micro and small agro-based enterprises should be established according to specific regional crops, so they can work closely with the agriculture sector and reap the benefits of easy availability of raw material.